A Comparison of Sprawl in the US and China: Applicability of Smart Growth Strategies to Chinese Cities. - Li, Zhi. (2017)
Abstract: This thesis identifies the differences in patterns and causes of sprawl between Chinese cities and US cities and examines the applicability of smart growth strategies to Chinese cities. Sprawl in the US is characterized as extensive dispersion at significantly low population densities. In contrast, sprawl in Chinese cities is characterized as excessive outlying expansion at high population densities and tendency towards both dispersion and fragmentation on urban fringe. Sprawl in the US is the consequences of both market force and public policy. Despite the market force, sprawl in China is mainly due to local governments' strong incentives to develop more land to collect land leasing fees for infrastructure development. Fragmentation in suburbs is also an unintended effect of protection of farmland. By analyzing four smart growth strategies, including Urban Growth Boundary, Priority Funding Area, Transit-Oriented Development and Brownfield Redevelopment, this study concludes that most smart growth strategies would only have limited effectiveness in curbing sprawl in China. To address sprawl in China, policies should focus on infill development, providing affordable housing in the inner city, encouraging urbanization and economic growth in the less developed areas, and ensuring a significant and long lasting local revenue source.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Weiping Wu.; Committee: Justin Hollander.; Keyword: Urban planning.